CORRELATION OF VITAMIN D WITH ANTIBODY QUANTITY IN IMMUNOPROPHYLACTIC INDIVIDUALS - Wiwis Wijayanti, Christina Destri; Ekawati, Evy Ratnasari; Pradana, Muhammad Sungging (Sean Institute, 2022)
The development of the field of health technology that integrates with advances in the economic field has provided an increase in life expectancy in populations in various countries today, but it is a life expectancy. this longer has its own effect in the form of an increase in cases of chronic diseases The preventive measures of a disease provide an individual's ability to stay healthy, happy and able to do activities freely. Immunoprophylactic is a powerful strategy in the primary prevention of a disease. The application of vaccination as an immunoprophylactic part is able to provide a protective effect related to the production of antibodies. The purpose of this study was to find out how the role of vitamin D is related to the formation of antibodies in individuals who have been vaccinated. The results showed that most of the study subjects had vitamin D levels within normal limits and to determine the formation of antibodies obtained the presence of production antibodies in each study subject using the immunofluorescent antibody detection method. Test the proximity of the relationship between the two variables using pearson correlation test from 25 research data. The pearson correlation test showed significance p=0.704 where p>0.05 indicated the absence of correlation between the assessed variables. The effect of vitamin D on immune cells, especially those related to the process of producing antibodies is very complex where the possibility of tolerogenic influence is one of the influencing factors. Vitamin D receptors are known to be mostly expressed by immune cells but there are differences in control related to cell activity status, for example vitamin D receptors can decrease in when differentiation occurs into macrophage cells or dendritic cells. The conclusions of the study showed that the concentration of vitamin D in most of the study subjects has not had a significant effect on the immunity system assessed based on the detection of levels antibodies.